Deflation-based identification of nonlinear excitations of the three-dimensional Gross-Pitaevskii equation - Boullé, N; Charalampidis, EG; Farrell, PE; Kevrekidis, PG (American Physical Society, 2020)
We present a number of solutions to the three-dimensional Gross–Pitaevskii equation describing atomic Bose-Einstein condensates. This model supports elaborate patterns, including excited states bearing vorticity. The coherent structures exhibit striking topological features, involving combinations of vortex rings and multiple, possibly bent vortex lines. Although unstable, many of them persist for long times in dynamical simulations. These solutions were identified by a state-of-the-art numerical technique called deflation, which is expected to be applicable to many problems from other areas of physics.